Electrocoagulation (EC) process to sustainably Treat Palm Oil Mill Effluent (POME) for wastewater reuse - Tahreen, Amina; Jami, Mohammed Saedi; Ali, Fathilah (2020)
Malaysia being one of the leading palm oil producers in the world has made enormous leaps in its production rate over the years. While the rising industry adds to the local economy, it is correspondingly generating a concerning amount of waste that is detrimental to the environment. Conventional methods for the treatment of palm oil mill effluent (POME) consist of advanced oxidation processes involving harsh chemicals, aerobic and anaerobic digestion systems, employing ponding systems before discharge into rivers. Large surface area is required for the ponding systems, involving long retention time and subsequent production of foul stench resulting in environmental pollution while the environmental discharge limits are unmet with high content of organic matter. This study aims to optimise the critical operational parameters namely current density, initial pH and time, using electrocoagulation (EC) to treat bio-treated POME, and investigate its reusability in the palm oil industry. EC is an attractive electrochemical process with simple set up, inexpensive and environmentally friendly procedure to remove pollutants by anode dissolution and therefore, carries a promising potential to be scaled up to treat huge amount of POME at the industrial level. Using aluminium electrodes with inter electrode distance of 10 mm on synthetic wastewater (representing biotreated POME), and a range of initial pH, current density and time of 3-8, 10-40 mA/cm2 and 15 to 60 minutes respectively, the effect of the three critical variables were investigated on the best chemical oxygen demand (COD) removal %. The highest COD removal of 71.5% was achieved at pH 6, current density 40 mA/cm2 and EC time of 15 minutes. The experiment was validated with real biotreated POME with the optimised parameters and resulted in the removal of 62.4% COD, 99.45 % turbidity, 99.1% total suspended solids and 92% of colour. The outcome of this study proved a significant reduction in the targeted pollution parameters in a very short time span of 15 minutes without the use of harsh chemicals or emission of harmful by-products, strongly overtaking the conventional processes. EC, therefore paves way to future membrane ultrafiltration integration to further enhance the treated effluent quality to meet reusable process water quality standards, to contribute a step further to reduce pollution and mitigate global fresh water scarcity.